The road from money to happiness - Gabriela Mihaela Mureșan; Melinda Timea Fülöp; Cristina Ciumaș (Journal of Risk and Financial Management, 2021)
Nowadays, companies must be concerned with the levels of satisfaction and happiness of employees. Hence, this paper proposes to investigate the links between salary and happiness through an exploratory study with a quasi-experimental design. The sample included 376 respondents, and we employed structured equation modeling (SEM) in ADANCO. Prior to evaluating the structural model, the goodness of fit shows moderate/excellent values. Our empirical results show a positive relationship between salary and happiness, salary and life satisfaction, salary and financial satisfaction, financial satisfaction and life satisfaction, and financial satisfaction and happiness. Thus, we consider that our research contributes to the literature by analyzing the relationship between income and happiness in a developing country such as Romania. Congruent with previous findings, we consider that our results provide evidence of the road from salary to happiness in developing countries.
Keywords: 330; happiness; money; satisfaction; SEM